Photoluminescent behavior of SrBi2Nb2O9 powders explained by means of beta-Bi2O3 phase - Volanti, D. P.; Cavalcante, L. S.; Paris, E. C.; Simoes, A. Z.; Keyson, D.; Longo, V. M.; de Figueiredo, A. T.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; De Vicente, F. S.; Hernandes, A. C. (American Institute of Physics (AIP), 2007)
Photoluminescence (PL) behavior of SrBi2Nb2O9 (SBN) powders was explained by means of beta-Bi2O3 phase on the SBN lattice. Oxygen vacancies and recombination of electrons holes in the valence band lead to the formation of [NbO5 center dot V-O(x)], [NbO5 center dot V-O(center dot)] and [NbO5 center dot V-O(center dot center dot)] complex clusters which are the main reason for the PL at room temperature. X-ray diffraction and Fourier transform Raman spectroscopy were used as tools to investigate the structural changes in SBN lattice allowing to correlate [NbO5 center dot V-O(center dot)]/[NbO6](') ratio with the evolution of the visible PL emission in the SBN powders. (c) 2007 American Institute of Physics.